Augmented Reality for Interactive, Innovative and Fun Science Learning: Systematic Literature Review - Arie Wahyu Prananta; Abdur Rohman; Risnawati Agustin; Nuridin Widya Pranoto (Jurnal Penelitian Pendidikan IPA, 2024)
The development of the learning process by utilizing current technological developments needs to adapt to the character of 21st-century learning. The fact that 21st-century learning is still not implemented optimally and well enough in schools has encouraged several studies that integrate Augmented Reality technology into science learning. AR Learning Media can visualize science learning concepts for understanding and structure of an object model, making AR a more effective, innovative, and fun media. Where the research objective is to examine Augmented Reality for Interactive, Innovative, and Fun Science Learning: Systematic Literature Review. The review was conducted based on state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. The results of this research explain that there are 3 types of Augmented Reality Methods, namely image recognition, Markerless Augmented Reality, Projection Augmented Reality, and Superimposition Augmented Reality; There are 4 things to use Augmented Reality, namely the use of augmented reality (AR) as a learning medium, the use of augmented reality (AR) to train skills, Abstract Thinking Skills, Creative Thinking Skills, Interactive, Innovative and fun. Some fields use AR, namely: entertainment, military training, robotics and telerobotics, consumer design, and medicine.